Suicide Trends in Sri Lanka 1880-2006; Social, Demographic and Geographical Variations - N Thalagala (College of Community Physicians of Sri Lanka, 2011)
Introduction Sri Lanka is noted for high suicide rates for many decades. Suicide rates over time indicate an epidemic currently in the settling phase. Despite the availability of a rich source of official statistics since very early years, an in-depth analysis is yet to be carried out. Methodology Suicide rates as reported to the Register general and Department of Police were compiled from 1880 to 2006. Then overall trends in suicide rates of Sri Lanka were described from 1880 to 2006. A more detailed analysis in relation to age, sex, ethnicity, religion, and geographical region are presented from 1961 to 2006. Results The long standing suicide epidemic of Sri Lanka seems to have passed its peak in the mid twentieth century and presently is on declining phase. Older persons, those 60 years and above, shared the largest suicide burden through out the period. Suicides among youths were not on the rise as observed in many other countries. Male to female ratio of suicides were on the increase and lies in the range of 2 to 3. Sinhalese Buddhists had the highest suicide rate followed by the Sri Lankan Tamils who were predominantly Hindus. Moors, who follow Islam, had the lowest suicide rates. The rural agricultural districts such as Vavunia, Polonnaruwa, Anuradhapura, Kurunegala, Matale, and Kegalle reported higher rates than rest of the country. Conclusions The suicide epidemic of the country seems to have past its‟ peak around the middle of the 20th century. Suicides among adult males have contributed to the major share of this rise in suicides. The general reduction of the suicide rates seen after mid nineteen nineties could be attributable to the policy thrusts initiated by the Presidential Taskforce on Suicide Prevention in 1997. Suicides remains to be a mental health priority even now. Keywords: suicide trends; suicide epidemiology; Sri Lanka mental health DOI: 10.4038/jccpsl.v14i1.2945 Journal of the College of Community Physicians of Sri Lanka Vol.14(1) 2009 24-32